Luke on trial: a literary analysis of the function of divine testing in Luke-Acts - Gulaker, Cato (Studies in biblical literature, 2024)
"This book presents a significant new reading of the function of divine testing in Luke-Acts. By using narrative criticism, fresh readings are provided on these texts, which are often deemed "difficult" or "unintelligible" by modern readers. Author Cato Gulaker argues that the many allusions to divine testing make good sense within the theological rationale of Luke, including the idea of praying to God in order for him not to lead his petitioners into temptation. As this element of the New Testament writings in general, and Luke in particular, is largely overlooked in academic publications, this book will be vital for scholars, clergy, and the general reader interested in this aspect of the theology and cosmology of the two-part Lukan narrative"--